2022
DOI: 10.1088/1741-2552/ac63ea
|View full text |Cite
|
Sign up to set email alerts
|

Wireless transmission of voltage transients from a chronically implanted neural stimulation device

Abstract: Objective. Consistent transmission of data from wireless neural devices is critical for monitoring the condition and performance of stimulation electrodes. To date, no wireless neural interface has demonstrated the ability to monitor the integrity of chronically implanted electrodes through wireless data transmission. Approach. In this work, we present a method for wirelessly recording the voltage transient (VT) response to constant-current, cathodic-first asymmetric pulsing from a microelectrode array. We imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…We developed a single printed circuit board-based neurostimulator system that simplified such issues while allowing for efficient stackup layer plan and crosstalk and coupling elimination. Application-specific IC-based neurostimulators can further miniaturize overall form-factors [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…We developed a single printed circuit board-based neurostimulator system that simplified such issues while allowing for efficient stackup layer plan and crosstalk and coupling elimination. Application-specific IC-based neurostimulators can further miniaturize overall form-factors [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to capture the electrode's voltage transients (VT) during constant‐current pulsing is of particular importance for ensuring that the electrode can deliver charge safely during stimulation without exceeding the potential limits associated with water electrolysis, electrode damage, or tissue damage. The VT data were wirelessly collected via the WFMA's reverse telemetry function for each of the 16 electrodes within each of the two WFMA devices, according to previously reported methods 14 . VT data were recorded at two time points; prior to device implantation, with the devices submerged in phosphate‐buffered saline (PBS: 0.126 M NaCl, 0.081 M Na 2 HPO 4 , 0.022 M NaH 2 PO 4 , pH 7.1–7.3), and for a second time, upon implantation in the spinal cord.…”
Section: Methodsmentioning
confidence: 99%
“…V acc is associated with the access resistance of the electrode. Previous studies have shown that V acc in vivo can be three to eight times larger than V access in PBS 14 . An example of a VT recorded from one of the electrodes is shown in Figure 5 and is labeled with each value of interest for assessing electrode performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation